Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae) - Zhang, Wei; Han, Na; Zhang, Min; Zhou, Chang-Fa (Zootaxa, 2019)
The detailed morphology and phylogenetic positon of Parafronurus youi Zhou & Braasch, 2003 have not been discussed especially so far. In this study, we re-describe and illustrate all stages in more detail. Compared to other genera in the subfamily Ecdyonurinae, the nymph of P. youi is characterized by rounded supracoxal spurs, rounded rectangular head capsule, dense setae on dorsal side of labrum, simple proximal and distal dentisetae, primarily swimming setae of caudal filaments. Upon the latter two characters, this genus seems closer to Asian Rhithrogeniella Ulmer, 1939.